The Effect of Distance Learning in the Pandemic on the Depression, Anxiety, Stress, and Occupational Commitment of Senior Nursing Students: A Crosssectional Study - Esin Çetinkaya Uslusoy; Eylem Paslı Gürdoğan; Berna Aksoy; Ezgi Kınıcı Dirik (Galenos Publishing House, 2024)
Objective: The study was conducted to determine the effects of distance learning during the pandemic on the depression, anxiety, stress, and professional commitment of senior nursing students. Method: This study is descriptive and cross-sectional design. The population of the study consisted of senior students and the sample consisted of students who agreed to participate in the study (n=235). Data were collected at the academic year 2020-2021. The data were obtained with the socio-demographic characteristics form, depression, anxiety, stress 21 scale, and the scale of commitment to professional in nursing. Results: As a result of the study, the mean depression level of the students was 7.05±4.42, the mean anxiety level was 5.44±4.24, the mean stress level was 7.42±4.01, and the mean score of the nursing professional commitment scale was 80.63±10.68. It was determined that female students feeling more stress than male students. In addition, there was a negative statistical relationship between increased depression, anxiety and stress and decreased professional commitment. Conclusion: It was observed that students' depression, anxiety and stress levels increased, and their professional commitment decreased due to distance education. It is recommended that nurse educators provide support to students against psychological changes and develop strategies that will increase their professional commitment.